2022
DOI: 10.1093/molbev/msac081
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Mutations and Transcript Errors in the Foodborne PathogenSalmonella entericasubsp.enterica

Abstract: Because errors at DNA level power pathogen evolution, a systematic understanding of the rate and molecular spectrum of mutations could guide the avoidance and treatment of infectious diseases. We thus accumulated tens of thousands of spontaneous mutations in 768 repeatedly bottlenecked lineages of 18 strains from various geographical sites, temporal spread, and genetic backgrounds. Entailing over ∼1.36 million generations, the resultant data yield an average mutation rate of ∼0.0005 per genome per generation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 75 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…Similar to the untreated results, the increased overall error rate between untreated and H 2 O 2 -treated wild-type Salmonella did not appear to be driven by any specific substitution error type. These observed differences in specific SNS type bias between studies could be attributed to different assay conditions, high-throughput sequencing methods, or genuine differences in the inherent substitution type biases between organisms [32]. Combined, these results suggest that there is no specific SNS type that is inherently driving the overall transcription error rates in wild-type compared to ΔgreAB Salmonella.…”
Section: Gre Factors Resolve Transcriptional Errors In Metabolic Gene...mentioning
confidence: 95%
See 1 more Smart Citation
“…Similar to the untreated results, the increased overall error rate between untreated and H 2 O 2 -treated wild-type Salmonella did not appear to be driven by any specific substitution error type. These observed differences in specific SNS type bias between studies could be attributed to different assay conditions, high-throughput sequencing methods, or genuine differences in the inherent substitution type biases between organisms [32]. Combined, these results suggest that there is no specific SNS type that is inherently driving the overall transcription error rates in wild-type compared to ΔgreAB Salmonella.…”
Section: Gre Factors Resolve Transcriptional Errors In Metabolic Gene...mentioning
confidence: 95%
“…The spots were air dried, and the TLC plates were placed into a chamber containing 0.9 M K 2 HPO 4 (pH 3.4). 32 P-labeled nucleotides in the TLC plates were visualized with phosphor screens on a phosphorimager (Bio-Rad), and relative nucleotide levels were quantified with the ImageJ software (NIH).…”
Section: Thin Layer Chromatographymentioning
confidence: 99%
“…First, we calibrated a log-normal DMR using data from the WS system. Assuming that the mean was equal to the observed average of E obs = 5 × 10 -11 gen -1 (Lind and Andersson, 2008; Foster et al, 2015; Long et al, 2015; Sung et al, 2015; Dettman et al, 2016; Sung et al, 2016; Schroeder et al, 2017; Long et al, 2018; Pan et al, 2022), we estimated the parameters of the log-normal DMR numerically based on the MPC-unevenness metric (Figure 4). We found that the data presented in Appendix B (Table 3) was compatible with values for parameter σ between 0.93 and 3.73 gen -1 (95%- CI).…”
Section: Resultsmentioning
confidence: 99%
“…The number and spectrum of mutations that have occurred over all generations can be determined using genome resequencing. Estimates of the average genomic mutation rate range from 0.8 × 10 -10 to 5.3 × 10 -10 bp -1 gen -1 for base pair substitutions, with the transition G:C>A:T being ten times more common than the transversion G:C>C:G, while insertion/deletion rates range from 0.2 × 10 -10 to 2.0 × 10 -10 bp -1 gen -1 (Lind and Andersson, 2008; Foster et al, 2015; Long et al, 2015; Sung et al, 2015; Dettman et al, 2016; Sung et al, 2016; Schroeder et al, 2017; Long et al, 2018; Pan et al, 2022). However, practical limitations imply that each of these estimates is typically based on an observation span of less than 100 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…The 151 clinical isolates from all set were selected based on the SNPs analysis defining a probable genetic relation with food isolates. The median fixation rate defined in this study for the core genome in Salmonella was three SNPs per year, therefore probable related isolates from the clinical surveillance per 20 years of surveillance were defined into the ~60 SNPs distance from a food isolate (32)(33)(34). were confirmed at the genus level, and the antimicrobial testing (AST) was performed by BD PhoenixTM automated microbiological system (Becton Dickinson Diagnostic Systems, Sparks, MD, USA).…”
Section: Methodsmentioning
confidence: 99%